Vertical Size Disparity and the Correction of Stereo Correspondence. (April 2013) - Mitsudo, Hiroyuki; Sakai, Ayumi; Kaneko, Hirohiko
We examined the stage of vertical-disparity processing that produces a global stereoscopic slant. In two psychophysical experiments, we measured perceived slant about a vertical axis for two-dimensional stereoscopic patterns consisting of random dots, concentric lines, and radial lines. Binocular image differences were introduced into each pattern by vertically magnifying either the entire image for the right eye or that for the left eye. Because the continuous lines were geometrically ambiguous in local stereo correspondence, the three patterns differed from each other in the local horizontal disparity measured in retinal coordinates. The two experiments revealed that, despite the differences in the retinal horizontal disparity, the slant settings were generally similar for the three patterns, in both short and long viewing distances (25 cm and 120 cm, respectively). These results are consistent with the idea that the visual system uses vertical disparity at least when establishing local stereo correspondence. A Bayesian model is proposed to account for the results.